IMPLEMENTASI PASAL 82 UU NO. 7 TAHUN. 1989 JIS UU NO. 3 TAHUN. 2006 JIS UU NO. 50 TAHUN 2009 PADA PERKARA PERCERAIAN (STUDI KASUS PADA PENGADILAN AGAMA KLAS 1. A PALU) - Ahmad Mirwan; Muhammad Akbar; Suhri Hanafi (Familia: Jurnal Hukum Keluarga, 2020)
This study aims to provide knowledge and understanding of the implementation of article 82 of Law no. 7 of 1989 JIS Law No. 3 of 2006 Law no. 50 of 2009 in divorce cases in Class I A Palu Religious Court, and how the efforts and solutions of Class I A Palu Religious Court in dealing with divorce. This research was designed using a type of field research, using a qualitative approach. After analyzing the research data, the final step of this research is checking the validity of the data with a view to proving that the research is truly valid. Results obtained from research in the Religious Courts concerning Implementation of article 82 of Law, no. 7 years. 1989 JIS Act. No. 3 years 2006 Law No. 50 years. 2009 concerning divorce cases is mandatory because it is a necessity to run it and has been implemented well as evidenced by existing data. The solution in dealing with divorce cases is to mediate and make trainings for judges to better understand the various cases in divorce.